Genre, conditions de travail et santé. Qu'est-ce qui a changé ? - Christelle Casse; Marianne De Troyer (European Trade Union Institute (ETUI), 2020)
– In Europe, despite equal treatment laws that mainly concern wages and non-discrimination between individuals, the gendered division of labour is still present: men and women do not work in the same professions and, when they work in similar occupations, their work activity, work experience, opportunities for professional promotion and remuneration are not the same. One of the justifications given for the collective inequalities observed between men and women in the workplace is the stereotype that women are generally assigned to less dangerous and less strenuous tasks. Occupational health policies and prevention practices also continue to be built on a model of gender neutrality of "workers" whose implicit referent is the male worker. This is why it is useful to analyse the obstacles and resistances to taking into account the gender dimension in occupational health, to produce data and studies to enrich knowledge on the differences in working conditions between men and women and their impacts on their health, and to propose interesting examples and alternatives. These are the objectives of this book.
Keywords: 330; equality policy; gender discrimination; Corporate Health Management; Gleichstellungspolitik; Geschlechterdiskriminierung; Betriebliches Gesundheitsmanagement